Versatile etherification of alcohols with allyl alcohol by a titanium oxide-supported molybdenum oxide catalyst: gradual generation from titanium oxide and molybdenum oxide. Issue 18 (2nd August 2018) - Kon, Yoshihiro; Fujitani, Tadahiro; Nakashima, Takuya; Murayama, Toru; Ueda, Wataru
Abstract : A sustainable method to synthesize allyl ethers from allyl alcohol by the simple mixing of TiO2 and MoO3 catalysts. Abstract : Etherification using allyl alcohol to produce allyl ether via dehydration is a fundamental technique for producing fine chemicals that can be applied to electronic devices. We demonstrate a sustainable method to synthesize allyl ethers from allyl alcohol with various alcohols up to a 91% yield, with water as the sole by-product. In this reaction, the active catalyst is gradually generated as the reaction proceeds through the simple mixing of TiO2 and MoO3 . The dispersion of MoO3 on the spent catalyst has been observed by XRD, HAADF-STEM, and STEM-EDS mapping. This catalyst shows excellent catalytic activity by virtue of the highly dispersed nature of MoO3 supported on TiO2, which is reusable at least five times. According to a mechanistic study including the measurement of XPS of MoO3 on TiO2 and control experiments using SiO2 and Al2 O3 supports, the suitable reducibility of MoO3 to coordinate the allyl moiety on TiO2 seems to be a key factor for high-yielding syntheses of various allyl ethers even under heterogeneous reaction conditions. The reaction mechanism is considered to be as follows: σ-allyl species are formed from dehydration of the allyl alcohol, followed by a nucleophilic attack by another alcohol against the σ-allyl carbon to give allyl ethers. The developed catalytic system should be suitable for easily handled syntheses of allyl ethers due to the employment of commercially available MoO3 and TiO2 with halide- and organic solvent-free reaction conditions.